We know that

$$\int_0^1 \int_0^1 x^y\,dy\,dx = \ln 2.$$

Do we know a closed-form of

$$\int_0^1 \int_0^1 \int_0^1 x^{(y^z)} \,dz\,dy\,dx\,?$$

As a start we know that

$$\int_0^1 x^{(y^z)}\,dz = \frac{\operatorname{Ei}(y \ln x) - \operatorname{li}(x)}{\ln y}.$$

Here $\operatorname{Ei}$ is the exponential integral, and $\operatorname{li}$ is the logarithmic integral.


First integrate with respect to $x$ i.e $$\int_0^1 \int_0^1 \int_0^1 x^{y^z}\,dx\,dy\,dz=\int_0^1 \int_0^1 \frac{1}{1+y^z}\,dy\,dz$$ Since $0<y<1$ and $0<z<1$, $$\int_0^1 \int_0^1 \frac{1}{1+y^z}\,dy\,dz=\sum_{k=0}^{\infty} (-1)^k \int_0^1 \int_0^1 y^{kz}\,dy\,dz=\sum_{k=0}^{\infty} \frac{(-1)^k\ln(1+k)}{k}$$ $$\begin{aligned} \sum_{k=0}^{\infty} \frac{(-1)^k\ln(1+k)}{k} & =1+\sum_{k=1}^{\infty} \frac{(-1)^k\ln(1+k)}{k} \\ &=1-\sum_{k=1}^{\infty} \frac{(-1)^{k-1}\ln k}{k}+\sum_{k=1}^{\infty} \frac{(-1)^k}{k}\ln\left(1+\frac{1}{k}\right) \\ \end{aligned}$$ The first sum is $-\eta'(1)$ where $\eta(s)$ is dirichlet eta function.

For the second sum: $$\begin{aligned} \sum_{k=1}^{\infty} \frac{(-1)^k}{k}\ln\left(1+\frac{1}{k}\right) &=-\sum_{k=1}^{\infty} \sum_{m=1}^{\infty} \frac{(-1)^k}{k}\frac{(-1)^{m}}{mk^m} \\ &=\sum_{m=1}^{\infty} \frac{(-1)^m}{m}(1-2^{-m})\zeta(m+1)\\ &=\sum_{m=1}^{\infty} \frac{(-1)^m}{m}\zeta(m+1)-\sum_{m=1}^{\infty} \left(\frac{-1}{2}\right)^{m}\frac{\zeta(m+1)}{m} \\ \end{aligned}$$ I am thinking of manipulating the following: $$\sum_{n=1}^{\infty} \zeta(n+1)x^n=-\gamma-\psi(1-x)$$ but I am not sure how to do that.


It seems that it does not have a closed-form...

Try $z$

$$\begin{aligned} {I_{zyx}} &= \iiint\limits_{{{[0,1]}^3}} {{x^{{y^z}}}{\text{d}}z\;{\text{d}}y\;{\text{d}}x}\\ &= \iint\limits_{{{[0,1]}^2}} {\frac{{{\text{Ei}}(y\log (x)) - {\text{li}}(x)}}{{\log (y)}}{\text{d}}y\;{\text{d}}x}\\ &= \int_0^1 {\left( {{{\log }_y}(2) - {{\log }_y}\left( {\frac{{y + 1}}{y}} \right)} \right){\text{d}}y} \quad \log y \mapsto r\\ &= \int_{ - \infty }^0 {\frac{{{e^r}}}{r}\left( {r - \log \left( {{e^r} + 1} \right) + \log (2)} \right){\text{d}}r} \end{aligned}$$

Try $y$

$$\begin{aligned} {I_{yxz}} &= \iiint\limits_{{{[0,1]}^3}} {{x^{{y^z}}}{\text{d}}y\;{\text{d}}x\;{\text{d}}z}\\ &= \iint\limits_{{{[0,1]}^2}} {{{(\log (x) + 1)}^{1 - z}}\Gamma \left( {\frac{1}{z}, - \log (x)} \right)\frac{{{\text{d}}x\;{\text{d}}z}}{z}} \end{aligned}$$

Try $x$

$$\begin{aligned} {I_{xyz}} &= \iiint\limits_{{{[0,1]}^3}} {{x^{{y^z}}}{\text{d}}x\;{\text{d}}y\;{\text{d}}z}\\ &= \iint\limits_{{{[0,1]}^2}} {\frac{1}{{{y^z} + 1}}{\text{d}}y\;{\text{d}}z}\\ &= \int_0^1 {\frac{{{\psi ^{(0)}}\left( {\frac{{z + 1}}{{2z}}} \right) - {\psi ^{(0)}}\left( {\frac{1}{{2z}}} \right)}}{{2z}}} {\mkern 1mu} {\text{d}}z\quad z \mapsto 1/r\\ &= \int_0^\infty {\frac{{{\psi ^{(0)}}\left( {\frac{r}{2}} \right) - {\psi ^{(0)}}\left( {\frac{{r + 1}}{2}} \right)}}{{2r}}} {\mkern 1mu} {\text{d}}r \end{aligned}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.